2021
DOI: 10.1108/aeat-06-2020-0126
|View full text |Cite
|
Sign up to set email alerts
|

Microwave absorption performance of hexagonal nano boron nitride doped basalt fabric-reinforced epoxy composites

Abstract: Purpose The purpose of this paper is to investigate the effect of doping element on the microwave absorption performance of hexagonal nano boron nitride (h-nBN)-reinforced basalt fabric (BF)/epoxy composites. A new type of hybrid composite that will be produced by the use of boron nitride as an additive that leads to increased radar absorption capability will be developed and a new material that can be used in aeronautical radar applications. Design/methodology/approach This study is focused on the microwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Strong microwave interference not only threatens human health, but also is harmful to electromagnetic equipment operation; therefore, microwave shielding technologies are important to high-precision devices, especially in the field of military, aerospace, and telecommunications [1][2][3]. Traditional metals and emerging shielding materials such as metal-organic framework architectures [4], basalt fabric/epoxy composites [5], or MXene composites [6][7][8][9][10] have good shielding effectiveness. Nevertheless, their opaqueness would limit applications in some fields of optoelectronics, for example, glass for stealth aircrafts or warships [11] or optical detection devices for medical and electronic security purposes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Strong microwave interference not only threatens human health, but also is harmful to electromagnetic equipment operation; therefore, microwave shielding technologies are important to high-precision devices, especially in the field of military, aerospace, and telecommunications [1][2][3]. Traditional metals and emerging shielding materials such as metal-organic framework architectures [4], basalt fabric/epoxy composites [5], or MXene composites [6][7][8][9][10] have good shielding effectiveness. Nevertheless, their opaqueness would limit applications in some fields of optoelectronics, for example, glass for stealth aircrafts or warships [11] or optical detection devices for medical and electronic security purposes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic (EM) wave absorbers can absorb EM energy, have potential in applications like RCS reduction, 1 RF energy harvesting, 2 EMI suppression, 3 and mutual coupling reduction between the antennas 4 . In addition, metamaterial enabled structures for various absorption mechanisms are also proposed 5–7 . A simple electric field‐driven LC resonator for near‐unity microwave absorption is demonstrated in Landy et al 8 Different absorbers for triple, 9 quad and multi‐bands 9–13 have been reported from microwave to optical regimes 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al proposed a dual-broadband reflective polarization converter which can achieve linear polarization in the lower frequency band of 7.74-14.44 GHz and circular polarization in the higher frequency band of 14.95-17.35 GHz [7]. Bakal et al designed a new type of hybrid composite to improve radar absorbtion capability, and it can used in radar applications [24]. Yang et al proposed a tri-band artificial electromagnetic polarization metasurface, which employed the equivalent circuit and surface current distribution to explain the polarization conversion physical mechanism [25].…”
Section: Introductionmentioning
confidence: 99%